Use of non-pneumatic anti shock garment in hemorrhagic shock - Bangal, Vidyadhar B.; Gavhane, Satyajit; Raut, Sonal; Thorat, Ujwala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Non-pneumatic anti-shock garment (NASG) is a first-aid device that reverses hypovolemic shock and decreases obstetric haemorrhage. It consists of articulated neoprene segments that close tightly with Velcro, shunting blood from the lower body to the core organs, elevating blood pressure and increasing preload and cardiac output. The use of an NASG can stabilize a patient while awaiting transport, during transport, or during delays in receiving care at referral facilities. Methods: A prospective observational study of use of non-pneumatic anti shock garment (NASG) in cases with obstetric hemorrhagic shock was carried out at a tertiary referral center. As soon as severe shock was recognized in the hospital, the anti-shock garment was placed. Data on various parameters related to use of NASG was collected and interpreted to draw conclusions. Results: NASG was used in 25 cases of hemorrhagic shock during one-year period. Post-partum hemorrhage (36%) was the commonest indication for NASG use, followed by ruptured tubal ectopic pregnancy (28%). It was observed that 68% and 32 % of women had shock index of 1-1.5 and above 1.5 respectively at the time of application of NASG. The shock index rapidly improved to 0.5-0.9 in 92% and 1-1.5 in 8 percent of cases respectively after the application of NASG. The NASG was mainly used in labour room (40%) and emergency department (36%). NASG was applied by nurses and doctors together in 64% of cases. NASG was kept for a period 24 hours in 92% cases. The survival rate was 96% following use of NASG. Conclusions: NASG is a temporizing alternative measure in hemorrhagic shock management that shows a trend to reduce hemorrhage related deaths and severe morbidities. NASG should be made available at all health facilities that deal with high risk pregnancies and deliveries.